Chronic Venous Insufficiency: prevalence and effect of compression stockings - Al Shammeri, Owayed M; AlHamdan, Nourah; Al-hothaly, Bushra; Midhet, Farid; Hussain, Mahboob; Al-Mohaimeed, Abdulrahman (International Journal of Health Sciences, 2014)
Introduction: Chronic venous insufficiency (CVI) is a common disease affecting mainly lower limbs and significantly influencing the quality of life. This study aims to estimate the prevalence of CVI in the Qassim Region and test the effectiveness of compression stockings as an intervention option. Methods: A cross sectional study was conducted to assess the prevalence of CVI among patients visiting primary health care (PHC) centers in the Qassim Region. CVI patients were diagnosed and classified using the clinical, etiologic, anatomical, and pathophysiological (CEAP) scale. They were randomly divided into two groups, one using compression stockings and the other standard medical therapy. A clinical follow up was done using multiple scale system including CEAP scale. Data analysis was performed using SPSS. Results: Among the 226 screened patients, 138 (61.1%) were diagnosed as having CVI (69% female and 45% male, p<0.001). Compared to the baseline, both the clinical and venous scores for CVI at the follow-up were significantly lower among patients using compression stockings, p=0.002 and p=0.003, respectively. Regression analysis suggested that, after controlling for age, sex and body mass index, compliance was the main factor responsible for a significant reduction in the clinical score among CVI patients. Conclusions: Chronic venous insufficiency is very common in the Qassim Region. Compression stockings are highly effective in improving clinical symptoms and signs of CVI. Trial registration: This study is registered at www.clinicaltrials.gov(NCT02050061). Â Â